OILADA DASTLABKI ODOB QOIDALARINI SHAKLLANTIRISHDA OTA-ONANING O‘RNI - Ibragimova, A.M. (SCIENCE and SOCIETY, 2023)
In this country, they talk about family relationshipsx and ix influence on the upbringing of the child, halts in a row in parental, sibling, sibling relationships in the formation of the moral education of children.
Keywords: family; family relations; parent-child relations; the role of the family and society; the role of morality and the upbringing of the child